Spontaneous Rupture of Pseudoaneurysm of Gastroduodenal Artery Complicating Pancreatitis: MDCT Diagnosis - Sah, PL; Rauniyar, RK; Gupta, RK; Dhungel, K; Ahmad, K; Gupta, MK (Nepalese Journal of Radiology, 2012)
Pseudoaneurysm of gastroduodenal artery is least common of all the splanchnic artery aneurysms. It occurs most commonly due to pancreatitis. Spontaneous rupture of the pseudoaneurysm has a high mortality rate. Pseudoaneurysm was traditionally diagnosed by conventional angiography. We report an interesting case of spontaneously ruptured pseudoaneurysm of gastroduodenal artery complicating pancreatitis diagnosed by multidetector computed tomography (MDCT) in a 50 years old man who presented with sudden onset of epigastric pain for 2 days. Contrast enhanced MDCT revealed a large hematoma surrounding pseudoaneurysm of the gastroduodenal artery. The patient was referred for embolization. Since rupture rate and mortality are high, prompt diagnosis of the ruptured pseudoaneurysm helps prevent or decrease mortality and morbidity. DOI: http://dx.doi.org/10.3126/njr.v1i1.6320 Nepalese Journal of Radiology Vol.1(1): 30-32